From Assistance to Dependency: The Influence of ChatGPT on the Authenticity of Academic Writing among Final-Year English Education Students - M Faiz; Mohammad Sofyan Adi Pranata (Fakultas Sastra - Universitas Muslim Indonesia, 2026)
The development of generative artificial intelligence technology, particularly ChatGPT, has transformed the way students complete various academic tasks, including the process of writing academic papers. The presence of ChatGPT offers various benefits, such as helping to develop ideas, correct grammar, and improve writing efficiency. On the other hand, the use of this technology has also raised concerns regarding the authenticity of academic writing and the potential for students to become dependent on artificial intelligence. This study aims to explore the impact of ChatGPT use on the authenticity of academic writing among final-year students in the English Education Program at Nurul Jadid University. The study employed a qualitative descriptive approach involving five senior students selected through purposive sampling. Data were collected via semi-structured interviews and analyzed using the interactive analysis model by Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and drawing conclusions. The results indicate that students use ChatGPT to assist with brainstorming, proofreading, grammar checking, paraphrasing, and developing academic arguments. Although the use of ChatGPT is considered capable of improving writing efficiency and quality, some participants acknowledged that excessive use has the potential to diminish the uniqueness of their writing style and their independence of thought. Nevertheless, the authenticity of the writing can still be maintained if students use ChatGPT as a tool, while the development of ideas, analysis, and academic decision-making remain under the writer’s control. These findings suggest that ChatGPT’s impact on the authenticity of writing is determined more by how students use it than by the technology itself.